Simulation study of the relative Askaryan fraction at the south pole - Paudel, Ek Narayan; Coleman, Alan; Schroeder, Frank G. (American Physical Society, 2022)
We use coreas simulations to study the ratio of geomagnetic and Askaryan radio emission from cosmic-ray air showers at the location of the south pole. The fraction of Askaryan emission relative to the total emission is determined by the polarization of the radio signal at the time of its peak amplitude. We find that the relative Askaryan fraction has a radial dependence increasing with the distance from the shower axis—with a plateau around the Cherenkov ring. We further find that the Askaryan fraction depends on shower parameters like the zenith angle and the distance to the shower maximum. While these dependencies are in agreement with earlier studies, they have not yet been utilized to determine the depth of the shower maximum, X$_{max}$, based on the Askaryan fraction. Fitting these dependencies with a polynomial model, we arrive at an alternative method to reconstruct X$_{max}$ using a measurement of the Askaryan fraction and shower geometry as input. Depending on the measurement uncertainties of the Askaryan fraction, this method provides a measurement of X$_{max}$ with a resolution similar to other methods of reconstructing X$_{max}$ from radio observables. Although existing template methods give superior resolution, they are more computationally intensive. Consequently, the use of polarization to extract the Askaryan fraction of the radio signal should be considered as an additional input observable in future generations of template-fitting reconstruction and other multivariate approaches for measuring X$_{max}$.